2008
DOI: 10.1007/s00284-007-9082-8
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Campylobacter jejuni Strains from Different Origins Under Oxidative Stress Conditions: Effect of Temperature

Abstract: Campylobacter jejuni is a microaerophilic pathogen but is able to survive oxidative stress conditions during its transmission to the human host. Strains of different origins (reference, poultry, or human clinical) were tested for survival under oxidative stress conditions. C. jejuni strains were grown in Mueller Hinton broth to obtain late exponential-phase cultures. Then they were exposed to 2 different stresses: (1) cultures were either plated on Columbia agar plates and exposed to atmospheric oxygen or (2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
1
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 20 publications
0
38
1
6
Order By: Relevance
“…C. jejuni lacks these osmoprotectant systems known to be present in other Gramnegative bacteria and research identifying similar systems that are induced by osmotic stress were not found (Garenaux et al 2008).…”
Section: Osmolaritymentioning
confidence: 98%
“…C. jejuni lacks these osmoprotectant systems known to be present in other Gramnegative bacteria and research identifying similar systems that are induced by osmotic stress were not found (Garenaux et al 2008).…”
Section: Osmolaritymentioning
confidence: 98%
“…estly thermophilic organism, C. jejuni survives optimally under a 12% CO 2 , 5% O 2 atmosphere at 37 to 42°C (24,61) and is sensitive to a spectrum of conditions, including aerobic, oxidative, heat, and osmotic stresses, as well as nutrient limitation (2,24,43). Many of these conditions are frequently encountered both inside and outside its natural animal hosts.…”
mentioning
confidence: 99%
“…Our study reveals that temperature downshifts up-regulate H. pylori napA expression at mid-log phase, which may increase survival of H. pylori in unfavorable environments. A cross-protection between the cold-shock response and oxidative-stress response might explain this increased resistance at low temperature (Garénaux et al, 2008).…”
Section: Helicobacter Pylori Expression Microarray Temperaturementioning
confidence: 99%